Swimming pool-type low-temperature heating reactor: recent progress in research and application. (September 2017) - Zhang, Yi-Xuan; Cheng, Hui-Ping; Liu, Xing-Min; Li, Jian-Min
Abstract: In this paper, we review the background and the recent development of the swimming pool-type low temperature heating reactor (SPLTHR). Particularly, we introduce the recent progress on the research of the technical feasibility, the economy, and the safety of the SPLTHR. Our conclusion suggests that the SPLTHR is mature in technique and competitive in economy. Moreover, it has an excellent inherent safety. We also propose a plan for the industry development of the SPLTHR.